Relationship Between Physical Activity, Healthy Lifestyle Behavior And Physical Fitness Of Palu City Esport Players - Rendy Rionaldy Iskandar Alam; Setya Rahayu; Agus Raharjo (STKIP Muhammadiyah Kuningan, 2023)
Research Objectives 1) Analyze the Level of Physical Fitness 2) Analyze the relationship between physical activity and physical fitness. 3) Analyze the relationship between healthy living behaviour and physical fitness. 4) Analyzing the relationship between physical activity, healthy living behaviour and physical fitness in Palu City sports players. This research is a quantitative correlational study; the sample in this study was esports players in Palu City, totalling 160 people. Data collection techniques and instruments used include questionnaires and multistage fitness test documentation. The variables in this study are physical activity, healthy living behaviour and physical fitness. Data analysis techniques use prerequisite tests and hypothesis testing. The results in this study are 1) The physical fitness level of esports players in Palu City is in a good category with a percentage of 76%. 2) The relationship between physical activity and physical fitness is in the weak correlation category. 3) The relationship between living behaviour and physical fitness is in the fragile correlation category. 4) The relationship between physical activity, healthy living behaviour, and physical fitness is in the weak correlation category. The conclusion of this study shows that the physical fitness level of Palu City sport players is in the sufficient category; the lack of physical activity and the application of healthy living behaviours greatly affect the quality of physical fitness of Palu City esports players